Thermal, radioactive and magnetic properties of the lavas of the Mt Melbourne Volcanic Field (Victoria Land, Antarctica) - Egidio Armadillo; Paolo Chiozzi; Massimo Verdoya; Vincenzo Pasquale, (Annals of Geophysics, 2009)
We present the results of measurements of physical properties carried out on mafic lavas from the Mt Melbourne Volcanic Field, useful for interpretation of geophysical surveys designed to shed light on the structure of the crust. The thermal conductivity is comparable to that of glass and shows a clear negative dependence on porosity. The volume heat capacity and the thermal diffusivity are less variable. The concentration of the thermally important natural radioactive isotopes was determined by gamma-ray spectrometry. Lavas denoted a rather low heat-production rate, and the largest concentration of heat-producing elements (potassium, uranium, thorium) was found in the trachyte samples. The magnetic susceptibility is more variable than the other physical properties and, among the several iron-titanium oxides, it appears primarily controlled by the ulvöspinel-magnetite solid solution series.